Simultaneous electrochemical deposition of nickel cobalt oxide-reduced graphene oxide composites for high performance asymmetric supercapacitors - KOCA, ATIF; BUDAK, ÖZLEM; UĞUZ NELİ, ÖZLEM (Elsevier Ltd, 2021)
In this work, a one-step electrodeposition approach was applied for nanosheets fabrication of binder free nickel cobalt oxide (NCO) and NCO-reduced graphene oxide (NCO-rGO) composites on the nickel-foam substrate by repetitive cyclic voltammetry (rCV). The NCO-rGO hybrids were firstly fabricated on Ni foam surface with the reduction of GO and electrodeposition of NCO simultaneously. Interaction of NCO particles with rGO sheets increased the conductivity of the composite and consequently facilitated the electron transfer rate. Electrochemical measurements proved that specific capacitance and cyclic performance of as-prepared materials were improved with the synergistic effect of rGO in the hybrid structure. The optimized NCO-rGO electrode exhibited a specific capacitance of 1916.5 F g−1 at 1 A g−1 with superior stability of 95.6% at a high current density of 10 A g−1 even after 3000 cycles. To explore its practical applications, an asymmetric supercapacitor (ASC) based on NCO-rGO as a positive electrode and rGO as a negative electrode was constructed, which exhibited a prominent specific energy of 45.22 Wh kg−1 at 400 W kg−1. As a result, NCO-rGO hybrid structure as the functional electrode material for the supercapacitors with remarkable electrochemical performance were obtained, thanks to the increased conductivity and decreased mass by removing binders. © 2021 Elsevier Ltd
Keywords: Hybrid nanostructure; Nickel-cobalt oxide; One-step electrodeposition; Reduced graphene oxide; Supercapacitor